Effect of land-use change and soil abandonment on microbial communities in Eastern Amazon Rainforest - Pedrinho, Alexandre (2018)
Land-use change threatens soil biodiversity in the Amazon Region. Over the last 40 years, the Amazon rainforest has lost a remarkable portion of its original cover. Forest has been converted into pasture through slash-and-burn process causing irreversible loss of plants and animals. However, the impact of land-use change on the soil microbial community and ecosystem functioning is still poorly understood. Here, we hypothesized that land-use change in Amazon region would affect soil physicochemical properties and, consequently, microbial composition and functions. We used DNA shotgun metagenome sequencing approach to assess soil microbial communities of three land-use systems, namely primary forest, pasture, and secondary forest in the Amazon region at the wet and dry seasons. Our data showed that the microbial community was influenced by the alterations in soil properties, with Al, Al saturation, water holding capacity, and pH significantly correlated to overall community structure and most of microbial phyla. Pasture was the most distinct site and presented the highest taxonomic and functional diversity in comparison with forest sites. Taxonomic changes were followed by functional changes in the community, with pasture presenting high abundance of sequences related to the metabolism of carbohydrates and stress response; primary forest soil hosted a high number of sequences related to the nitrogen metabolism; while secondary forest soil included abundant genes related to respiration and sulfur-metabolism. Although taxonomic structures were very distinct between the three sites, we observed a recovery of the functional profile in secondary forest after pasture abandonment. This observation was evidenced by network analysis, where the two forest sites presented similar key microbial groups dominating the core correlations